The Regional Centralization of Electronic Fetal Heart Rate Monitoring and Its Impact on Neonatal Acidemia and the Cesarean Birth Rate - Kaori Michikata; Hiroshi Sameshima; Hirotoshi Urabe; Syuichi Tokunaga; Yuki Kodama; Tsuyomu Ikenoue (Hindawi Limited, 2016)
Objective. The improvement of the accuracy of fetal heart rate (FHR) pattern interpretation to improve perinatal outcomes remains an elusive challenge. We examined the impact of an FHR centralization system on the incidence of neonatal acidemia and cesarean births. Methods. We performed a regional, population-based, before-and-after study of 9,139 deliveries over a 3-year period. The chi-squared test was used for the statistical analysis. Results. The before-and-after study showed no difference in the rates of acidemia, cesarean births, or perinatal death in the whole population. A subgroup analysis using the 4 hospitals in which an FHR centralization system was continuously connected (compliant group) and 3 hospitals in which the FHR centralization system was connected on demand (noncompliant group) showed that the incidence acidemia was significantly decreased (from 0.47% to 0.11%) without a corresponding increase in the cesarean birth rate due to nonreassuring FHR patterns in the compliant group. Although there was no difference in the incidence of nonreassuring FHR patterns in the noncompliant group, the total cesarean birth rate was significantly higher than that in the compliant group. Conclusion. The continuous FHR centralization system, in which specialists help to interpret results and decide clinical actions, was beneficial in reducing the incidence of neonatal acidemia (pH < 7.1) without increasing the cesarean birth rate due to nonreassuring FHR patterns.